The role of ultrasound in root canal treatment and retreatment: Literature review (Research, Society and Development, 2025)
Endodontic treatment aims to preserve the tooth within the oral cavity, maintaining its function and preventing complications in the periradicular tissues. This literature review aimed to evaluate the effectiveness of ultrasound in the different stages of root canal treatment, focusing on promoting greater clinical safety and efficiency. Studies available in the PubMed, CAPES, SciELO, Google Scholar, and Virtual Health Library (BVS) databases that addressed the application of ultrasound in endodontics were analyzed. The results demonstrated that the use of ultrasound is beneficial in various phases of treatment, such as access to the pulp chamber, location of obliterated canals, removal of intraradicular posts and fractured instruments, as well as aiding in canal disinfection and removal of filling materials during retreatment. Based on the data collected, it is concluded that ultrasound is an effective and safe tool, contributing to increased predictability and success of endodontic procedures. The objective of this work is to analyze the applicability of ultrasound as an auxiliary technology in endodontic treatment.